2015
DOI: 10.1016/j.jegh.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Role of patient-reported outcomes and other efficacy endpoints in the drug approval process in Europe (2008–2012)

Abstract: The present study aimed at systematically reviewing the role and extent of patient-reported outcomes (PROs) usage within the package of scientific evidence considered for marketing authorization (MA). All regulatory information published by the European Medicines Agency (EMA) for products authorized between January 2008 and December 2012 and appearing in the European Public Assessment Report (EPAR) database was examined for efficacy endpoints. The endpoints here considered included: PROs, clinician reported ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
0
20
0
2
Order By: Relevance
“…PROs were the primary trial endpoint for nearly 31% of products with PRO claims, which is slightly below the 37% reported for all EMA approvals in a previous study [12]. However, it is much less than the 71% and 76.7% reported for all new FDA approvals with PRO claims [7,10] and the 86% reported for FDA orphan drug approvals with such claims (Table 2) [9].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…PROs were the primary trial endpoint for nearly 31% of products with PRO claims, which is slightly below the 37% reported for all EMA approvals in a previous study [12]. However, it is much less than the 71% and 76.7% reported for all new FDA approvals with PRO claims [7,10] and the 86% reported for FDA orphan drug approvals with such claims (Table 2) [9].…”
Section: Discussionmentioning
confidence: 72%
“…Additionally, 21.7% of orphan-designated approvals in the studied sample presented PRO claims in their SmPCs. This is significantly below the 47% reported PRO claims for all new drug approvals by the EMA from 2006 to 2010 [11] and the 46% reported from 2008 to 2012 [12]. Conversely to the above mentioned studies, which analysed the entire content of the European Public Assessment Reports (EPARs), we focused only on the SmPCs, because they include PRO claims granted by the EMA.…”
Section: Discussionmentioning
confidence: 97%
“…There is evidence supporting the inclusion of patient-reported outcomes, including health-reported QoL, in regulatory product approvals [ 15 , 17 – 19 ]. Vodicka et al investigated the entries in the US clinicaltrials.gov register between 2007 and 2013 and reported an increase in the collection of patient-reported measures from 2009 onwards, particularly oncology drug trials [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…To a large extent, such acceptance has been fuelled by clinicians, patients and caregivers [ 15 – 17 ]. Two different studies found that one-third of the EMA reports included patient reported measures among which QoL data, with the latter being more frequently mentioned in reports of antineoplastic agents [ 18 , 19 ]. A similar trend is observed at the Food and Drug Administration (FDA) where a draft guidance on the use of patient-reported outcomes in industry-sponsored studies was released for public consultation by the FDA in early 2006 and later updated in 2009 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The number of patient‐reported scales has been increasing in the last several years, as neurological examination, electrophysiological, imaging, and laboratory test findings do not include significant information regarding patients' experiences, and they are inadequate to assess quantitatively several important disease components, such as pain and fatigue . However, as some of these scales are time‐consuming, they may not be feasible in situations in which time is limited.…”
Section: Introductionmentioning
confidence: 99%